2022
DOI: 10.3390/ph15101176
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Effect of Steroids for Hearing Preservation in Cochlear Implantation: Conclusions Based on Three Cochlear Implant Systems and Two Administration Regimes

Abstract: The main aim of this study was to assess the clinical effect of steroids (dexamethasone and prednisone) on hearing preservation in patients who underwent cochlear implantation with different cochlear implant systems (Oticon®, Advanced Bionics®, Med-El®). 147 adult patients met the inclusion criteria and were enrolled to the study and divided into three groups depending on the brand of cochlear implant they received and participated in all follow-up visits regularly. They were also randomly divided into three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…However, this may be due to other factors such as the patient's comorbidities (50). When comparing the effects of IV dexamethasone, combined PO prednisone and IV dexamethasone, and no steroid administration using different CI systems, HP was demonstrated in the steroid therapy groups (10). In addition, Wanna et al (51) showed that patients administered postoperative PO steroids had improved HP outcomes than patients who did not receive steroids.…”
Section: Steroid Management For Cochlear Implantation E31mentioning
confidence: 99%
See 3 more Smart Citations
“…However, this may be due to other factors such as the patient's comorbidities (50). When comparing the effects of IV dexamethasone, combined PO prednisone and IV dexamethasone, and no steroid administration using different CI systems, HP was demonstrated in the steroid therapy groups (10). In addition, Wanna et al (51) showed that patients administered postoperative PO steroids had improved HP outcomes than patients who did not receive steroids.…”
Section: Steroid Management For Cochlear Implantation E31mentioning
confidence: 99%
“…4). This discrepancy may be due, in part, to an increase in published research supporting steroid usage and limited studies studying steroid tapering in CI (1,(9)(10)(11)(12)22,(51)(52)(53)(54).…”
Section: Steroid Taper Utilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinically, glucocorticoids are usually used to prevent postoperative fibrosis 9 . However, its long‐term control of fibrosis was not validated for all cases 10 …”
Section: Introductionmentioning
confidence: 99%